2021
DOI: 10.1016/j.sleepx.2021.100037
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation in two Saskatchewan First Nation communities: a public health consideration

Abstract: Objectives Sleep deprivation is a common problem in Canada and is associated with many health problems. More than a quarter of Canadians get fewer than the recommended sleep hours (<7 h). This paper examines the prevalence and risk factors for sleep deprivation in two First Nation communities in Saskatchewan, Canada. Methods The baseline cross-sectional survey was completed between 2018 and 2019 in collaboration with the two Cree First Nation communities in Saskatchewan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Duration of sleep was available for 96% (567/588) of the adults who participated. The mean reported duration of sleep was 8.18 ± 2.28 h, and the median sleep duration was 8.00 h. The prevalence of sleep deprivation was 25.4% (144/567) [32,33].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Duration of sleep was available for 96% (567/588) of the adults who participated. The mean reported duration of sleep was 8.18 ± 2.28 h, and the median sleep duration was 8.00 h. The prevalence of sleep deprivation was 25.4% (144/567) [32,33].…”
Section: Resultsmentioning
confidence: 96%
“…A total of 588 participants completed the baseline survey: 418 individuals from Community A and 170 individuals from Community B. Demographic information about the participants was presented elsewhere and is only briefly described here [32,33]. Mean age ± SD of the 588 study participants was 40.0 ± 15.3 years, and the age was in the range of 18-78 years.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline survey of the First Nations Sleep Health Project (FNSHP) was completed between 2018 and 2019 in collaboration with two Cree First Nation communities (Community A and Community B) in Saskatchewan, Canada. The methods were presented elsewhere [ 16 , 17 , 18 ] and are briefly described here. The overall goal of the FNSHP was to study the relationships between sleep disorders, risk factors and co-morbidities, and to evaluate local diagnosis and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Daytime sleepiness among residents of the communities was related to respiratory comorbidities and indices of poverty [11]. Sleep deprivation among community residents who participated in our project was related to housing conditions [12]. Studies in the USA have indicated higher rates of sleep disorders among American Indians compared with other ethnic groups [13,14].…”
Section: Introductionmentioning
confidence: 99%